CXCL13 Neutralization Attenuates Neuropsychiatric Manifestations in Lupus-Prone Mice - Michelle W. Huang (Frontiers Media S.A., 2021)
Neuropsychiatric lupus (NPSLE), the nervous system presentation of systemic lupus erythematosus (SLE), remains challenging to treat due to its unclear pathogenesis and lack of available targeted therapies. A potential contributor to disease progression is brain tertiary lymphoid structures (TLS); these ectopic lymphoid follicles that can develop tissue-targeted antibodies have recently been described in the MRL/lpr lupus mouse strain, a classic model for studying NPSLE. The brains of MRL/lpr mice show a significant increase of CXCL13, an important chemokine in lymphoid follicle formation and retention that may also play a role in the disease progression of NPSLE. The aim of the present study was to inhibit CXCL13 and examine the effect of this intervention on lymphoid formation and the development of neurobehavioral manifestations in lupus mice. Female MRL/lpr mice were injected with an anti-CXCL13 antibody, an IgG1 isotype-matched antibody, or PBS either three times a week for 12 weeks intraperitoneally (IP) starting at 6-8 weeks of age, or continuously intracerebroventricularly (ICV) with an osmotic pump over a two-week period starting at 15 weeks of age. Cognitive dysfunction and depression-like behavior were assessed at the end of treatment. When treatment was delivered IP, anti-CXCL13 treated mice showed significant improvement in cognitive function when compared to control treated mice. Depression-like behavior was attenuated as well. Furthermore, mice that received anti-CXCL13 by the ICV route showed similar beneficial effects. However, the extent of lymphocyte infiltration into the brain and the general composition of the aggregates were not substantively changed by anti-CXCL13 irrespective of the mode of administration. Nevertheless, analysis of brain gene expression in anti-CXCL13 treated mice showed significant differences in key immunological and neuro-inflammatory pathways that most likely explained the improvement in the behavioral phenotype. Our results indicate that CXCL13 affects the behavioral manifestations in the MRL/lpr strain and is important to the pathogenesis of murine NPSLE, suggesting it as a potential therapeutic target.